Improving the Ability of Formulating High-Level Questions Through the Discussion-Comparison Method with Critical Analysis - Irwandi Irwandi; Rusdi Hasan (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Prospective teachers are less able to formulate high-level questions, so that the skills of teachers to formulate high-level questions are still lacking, even though it really determines students' critical thinking abilities. This study aims to determine whether there is an increase in students' ability to formulate high-level questions through the discussion-comparison method 1,2 with critical analysis of articles in the Biology Education Study Program, University of Muhammadiyah Bengkulu. Methods: This research used the Classroom Action Research (CAR) method with four cycles. Results: The results showed that there was an increase in the ability to formulate high-level questions of students through the discussion-comparison method 1,2 with critical analysis of articles in the Biology Education Study Program, University of Muhammadiyah Bengkulu.